Synthesis and anti‐inflammatory effects of novel emodin derivatives bearing azole moieties. Issue 2 (30th December 2019) - Zhu, Xiaokang; Chen, Qifang; Yang, Yujin; Ai, Xixi; Chen, Si; Song, Yang
Abstract: Twelve azole derivatives of emodin were designed to possess anti‐inflammatory activity and synthesized via a two‐step sequence composed of the Williamson ether reaction and N ‐alkylation. The anti‐inflammatory properties of these compounds were evaluated in RAW264.7 cells by measuring lipopolysaccharide (LPS)‐induced nitric oxide (NO) production. The introduction of imidazole and four carbons into the scaffold of emodin led to the discovery of the potent compound 7e, which showed the best inhibition of NO production among twelve analogs. In our experiential setting, the IC50 of compound 7e in NO production is 1.35 µM, which is lower than that of indomethacin. Mechanically, compound 7e effectively inhibited the protein and messenger RNA expressions of cyclooxygenase‐2 and inducible NO synthase, as well as that of the proinflammatory cytokine interleukin‐6, and the cytokines interleukin‐1β and tumor necrosis factor‐α in the LPS‐stimulated RAW 264.7 macrophages. Compound 7e exerted inhibitory effects on the nuclear factor κB pathway by reducing the LPS‐induced phosphorylation of the inhibitor of NF‐κB and the nuclear translation of p‐p65. These results suggest the potential of compound 7e in improving inflammatory conditions and diseases. Abstract : Twelve azole derivatives of emodin were designed to possess anti‐inflammatory activity and synthesized via the Williamson ether reaction followed by N ‐alkylation. The anti‐inflammatory properties of these compounds were evaluated in RAW 264.7 cells. Compound 7e showed the best inhibition of NO production among the twelve analogs. The mechanistic effects of compound 7e were elucidated in detail